The Shifting Trends in Baby Naming: An Anthropolinguistic Perspective on the Popularity of the Name "Muhammad" in England and Wales - El-Warits, Aden Achmaduddin Kamil; Hakim, M. Lukmanul; Rifqi, Muhammad Nabil; Buana, Cahya (Kalimatuna: Journal of Arabic Research, 2024)
This study examines the rising popularity of the name of "Muhammad" in England and Wales through an anthropolinguistic lens. This phenomenon reflects the social, cultural, and demographic dynamics resulting from the growth of the Muslim population in the region. Using a qualitative approach, the study analyzes statistical data and interviews with local Muslim communities to understand the meaning behind the choice of this name. The findings indicate that the name "Muhammad" not only represents religious and cultural identity but also signifies societal acceptance of diversity. This article contributes to a deeper understanding of the relationship between language, culture, and social change in the context of multicultural societies.